PENERAPAN ATURAN PERBUATAN BERLANJUT DALAM PUTUSAN PERKARA PIDANA - Alif Oksaryan Mulyana; Diana Lukitasari (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2022)
Abstract: The application of the concursus is not an easy thing because one formulation and the other Concursus formulations have similarities, so in its application, it is necessary to be careful and thorough with judges in deciding and applying which concursus rules will be used, therefore This article purpose of examining and answering the problem of how to apply the provisions of Article 64 of the Criminal Code regarding continuing actions in criminal case decisions. This legal research is prescriptive normative legal research. The approach used is statutory. The data collection technique used is a literature study. The data analysis technique uses the syllogism method with a deductive mindset. Based on the results of the research conducted by the author, it can be concluded that in continuing actions there is a